2019
DOI: 10.1089/bio.2018.0079
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Professionalization of Biobank Business Operations: A Worldwide Survey

Abstract: Quality specimens from biobanks are key resources to support reproducible research. Sustaining biobanks requires robust management. We recently published a pilot survey that indicated that over half the participating biobanks had business plans in place and another third were working on business planning. While the results provided a clue to the status of business planning in biobanking, it was concluded that a longer and more indepth survey and analysis were required. In April 2017, an extended survey was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…10 Biobanks that apply robust business management, as well as scientific best practices and standards, are consistent with high quality ''modern biobanking.'' [11][12][13][14] The SARS-CoV-2 virus has spread rapidly around the world and affected nations with COVID-19 disease on varying timelines. Currently, the COVID-19 pandemic continues at different stages in different countries with different effects on their health care systems.…”
Section: Role Of Biobanks and Their Challenges During The Covid 19 Pamentioning
confidence: 99%
See 1 more Smart Citation
“…10 Biobanks that apply robust business management, as well as scientific best practices and standards, are consistent with high quality ''modern biobanking.'' [11][12][13][14] The SARS-CoV-2 virus has spread rapidly around the world and affected nations with COVID-19 disease on varying timelines. Currently, the COVID-19 pandemic continues at different stages in different countries with different effects on their health care systems.…”
Section: Role Of Biobanks and Their Challenges During The Covid 19 Pamentioning
confidence: 99%
“…As mentioned before professionally-organized biobanks with a clearly focused business plan will have competitive advantage to leverage. 7,[11][12][13][14]51 Responding to the research needs of the COVID-19 pandemic has been a major scientific, organizational, and financial challenge with an uncertain outcome. If prepared,…”
Section: Sustainability Of Biobanksmentioning
confidence: 99%
“…Most importantly, this approach reduces potential exposure by diminishing transfer of biohazardous materials, limiting the number of additional specimens needed for collection, and adhering to biosafety guidelines. Further, it creates the potential to generate a holistic, statistically powered, and standardized cohort characterization by compiling all results in one bank, and it fosters important long-term follow up by overcoming the well-documented issues with decentralized biobank sustainability [6][7][8][9][10][11][12][13][14] . The creation of this resource at NYULH has enriched the community with high-quality patientlinked COVID-19 specimens, which has already contributed to novel findings about SARS-CoV-2 epidemiology 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The survey results focused on the status of business planning were analyzed and submitted for publication as the main analysis. 13 The current analysis extends the business operations planning by reviewing and interpreting the results of the questions on performance metrics and utilization, as they relate to sustainability. As is customary with these types of surveys, the data reported by the participants were assumed to be given.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve a greater sample size and to ensure better representation of the global community, we decided to extend the scope of the survey and do more extensive sampling of biobanks worldwide. Recently, we reported these initial findings, 13 looking at sustainability and business planning in research biobanks in terms of how that related to advanced professionalization of biobank business operations. We reported that organizations that support biobanks have increasingly recognized the need to professionalize their management, staffing, and operations, particularly those with large collections and a drive to work with industry.…”
Section: Introductionmentioning
confidence: 98%